Effects of gold and copper mining on the structure and diversity of the surrounding plant communities in Northeast Tiger and Leopard National Park - Wang, Xue; Li, Yue; Bai, Xueyuan; Sheng, Lianxi; Zhang, Houling; Chen, Faping; Xiao, Yujun; Liu, Wenze; Zhai, Yuquan (Frontiers in Plant Science, 2024)
Northeast China Tiger and Leopard National Park is home to the largest and only breeding family of wild tigers and leopards in China. The mining of open-pit gold and copper mines in the core zone might affect the surrounding forest ecosystem and the survival activities of wild tigers and leopards. In order to understand the impacts of gold and copper mining on the structure and diversities of the surrounding plant communities, the vegetation of the forest layer, shrub layer and herb layer of the forest community in the original forest area, mining area, tailings area and restoration area of the Northeast China Tiger and Leopard National Park were investigated, and the influence of plant community structure on species diversity was also evaluated. This study concluded that there are 25 species belonging to 11 families, 16 genera of trees, 43 species belonging to 22 families, 35 genera of shrubs, and 57 species belonging to 23 families, 46 genera of herb in the sampling sites. There were no significant differences in the community structure characteristics and species diversities of the tree layer and the shrub layer in different operational areas. However, in herb layer, the heights, the coverage and the species diversity index were higher in the restoration area. Additionally, the community structure was one of the major factors that influence the diversity indices, which might be an important way for mining to impact plant diversity. Therefore, mining had some impacts on the structure and diversity of the surrounding plant communities, but the impacts did not reach a significant level. These results could provide scientific support for the management of the forest ecosystems around the mining area of Northeast Tiger and Leopard Park.